2010
DOI: 10.2353/ajpath.2010.100063
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis-Induced Experimental Pulmonary Hypertension

Abstract: The mechanisms underlying schistosomiasis-induced pulmonary hypertension (PH), one of the most common causes of PH worldwide, remain unclear. We sought to determine whether Schistosoma mansoni causes experimental PH associated with pulmonary vascular remodeling in an interleukin (IL)-13-dependent manner. IL-13R␣1 is the canonical IL-13 signaling receptor, whereas IL-13R␣2 is a competitive nonsignaling decoy receptor. Wild-type, IL-13R␣1 ؊/؊ , and IL-13R␣2 ؊/؊ C57BL/6J mice were percutaneously infected with S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 50 publications
3
84
0
Order By: Relevance
“…The infection was done by placing the mice's tails in a vial containing 30-35 cercariae for 30 minutes. 132 Fifty-five days later, mice were challenged intravenously by injection of 5,000 viable eggs (suspended in 0.5 mL of sterile saline) into the tail vein. This intravenous challenge mimicked the deposition of eggs in the lung by collateral shunts, which normally form in chronically infected mice.…”
Section: Chp Combined With Su-5416mentioning
confidence: 99%
“…The infection was done by placing the mice's tails in a vial containing 30-35 cercariae for 30 minutes. 132 Fifty-five days later, mice were challenged intravenously by injection of 5,000 viable eggs (suspended in 0.5 mL of sterile saline) into the tail vein. This intravenous challenge mimicked the deposition of eggs in the lung by collateral shunts, which normally form in chronically infected mice.…”
Section: Chp Combined With Su-5416mentioning
confidence: 99%
“…Perivascular infi ltration of infl ammatory cells around remodeled vessels has consistently been demonstrated in animal models of PAH, including the mouse model of Sch-PAH and in patients with IPAH [ 43 ]. The cells involved are T-cells, macrophages, B cells, mast cells, and dendritic cells in the adventitia and media of muscular pulmonary arteries.…”
Section: Pathogenesismentioning
confidence: 95%
“…The injection of eggs alone was not suffi cient to cause right ventricular hypertension, so the embolic disease alone does not seem to cause experimental PAH [ 43 ]. Studies with lung samples collected at autopsies of individuals with Sch-PH demonstrated pulmonary vascular remodeling with plexiform lesions and arterial medial thickening in all 18 samples examined, but failed to fi nd eggs of the parasite.…”
Section: Pathogenesismentioning
confidence: 98%
See 1 more Smart Citation
“…Observations suggest that chronic HIV-associated inflammation leads to an accumulation of asymmetrical dimethylarginine, which is a well-known endogenous inhibitor of endothelial nitric oxide synthase, and, thus, promotes endothelial dysfunction and vascular smooth muscle cell proliferation. [63][64][65] Additionally, Nef and Tat proteins modulate the release of IL-2 and monocyte chemotactic protein-1 (MCP-1, also known as CCL2), which stimulate pulmonary vascular remodeling, 66,67 particularly in Schistosomiasis infection 68,69 ( Figure 2). Whether overlap in cytokine activation patterns in Schistosomiasis and HIV is responsible for PAH in coinfected patients, however, requires further investigation.…”
Section: Contemporary Hypothesesmentioning
confidence: 99%